2016
DOI: 10.1016/j.vetmic.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of highly and low pathogenic avian influenza viruses to chickens, ducks, tree sparrows, jungle crows, and black rats for the evaluation of their roles in virus transmission

Abstract: 25Highly pathogenic avian influenza viruses (HPAIVs) have spread in both poultry and wild 26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Overall, MOC-Du were shown, with all three methods, to be less susceptible in vitro for IAV-infection compared to MOC-Ch and MOC-Tu independent of the investigated influenza subtype. In vivo studies previously reported that ducks were less susceptible to LPAIV in comparison to other birds including domestic poultry, jungle crows, and tree sparrows (Hiono et al, 2016); whereas, authors did not investigate the reproductive tract. Possible differences in viral binding and replication of human-adapted virus pH1N1 and avian adapted viruses H9N2 and H6N8, could be the variation in the expression pattern of α2,3 and α2,6 sialic acids in the epithelial layer (Pillai and Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, MOC-Du were shown, with all three methods, to be less susceptible in vitro for IAV-infection compared to MOC-Ch and MOC-Tu independent of the investigated influenza subtype. In vivo studies previously reported that ducks were less susceptible to LPAIV in comparison to other birds including domestic poultry, jungle crows, and tree sparrows (Hiono et al, 2016); whereas, authors did not investigate the reproductive tract. Possible differences in viral binding and replication of human-adapted virus pH1N1 and avian adapted viruses H9N2 and H6N8, could be the variation in the expression pattern of α2,3 and α2,6 sialic acids in the epithelial layer (Pillai and Lee, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the virus growth in chickens, growth of A/black swan/Akita/1/2016 (H5N6) virus was slightly lower in ducks than that by A/chicken/Kumamoto/1‐7/2014 (H5N8), which has been studied by Kanehira et al . and Hiono et al . .…”
Section: Discussionmentioning
confidence: 99%
“…The tissue tropisms of these isolates in ducks were similar to that of A/duck/Anyang/AVL‐1/2001 (H5N1) as previously reported (Tumpey et al., ). Some HPAIVs replicate systemically and cause mortality; however, ducks are often clinically healthy or mildly diseased when infected with HPAIVs (Kishida et al., ; Hiono et al., ). Factors influencing the clinical course of HPAIV‐infected ducks depend on species, breeds, age and virus strain, and the presence of HPAIV in skeletal muscles is not related to the ability to cause disease in waterfowl (Pantin‐Jackwood & Suarez, ; Pantin‐Jackwood, Suarez, Spackman, & Swayne, ).…”
Section: Discussionmentioning
confidence: 99%